LC-MS/MS Analytical Method Development and Validation for Determining Vinamidinium HexafluoroPhosphate Impurity in Etoricoxib - Ganta, Satish; Siva Rao, T; Rama Srinivas, K; Suman, Pallapati (Indian Journal of Pharmaceutical Education and Research, 2023)
Background and Aim: Process impurities may adversely affect the efficacy, excellent quality, and safety of pharmaceutical drugs. Ultimately, the purpose of this research work was to develop and validate a LC-MS/MS-based method for determining the Vinamidinium hexafluorophosphate impurity (VHP) in Etoricoxib in a simple, specific, accurate, and precise manner. Materials and Methods: To elute the Vinamidinium hexafluorophosphate impurity in Etoricoxib at a flow rate of 0.5mL/min within 20.0 min of runtime, a Symmetry Shield RP18, 5µm column with a 150 x 3.9 mm internal diameter was utilized in binary gradient mode. The buffer solution, which contained formic acid (0.1%) and acetonitrile (100%), as well as a diluent solution of acetonitrile (50%) and water (50%), was used to achieve the chromatographic separation. A triple quadrupole mass spectrometer (Shimadzu LC/MS/MS 8040) in Multiple Reaction Monitoring (MRM) mode was needed to monitor the results. Results and Discussion: The method's linearity was evaluated at levels from 25% to 150%, and the R2 value was discovered to be 0.99. Sensitivity values of 0.04µg/g (LOD) and 0.13µg/g (LOQ) were established. The recovery of impurity levels of Vinamidinium hexafluorophosphate ranges from 70.0% to 130%. Linearity, specificity, accuracy, LOD, LOQ, and precision of the method were all validated. Within the assay variability limitations, it was found that the intra- and inter-day precision values were 0.67%, and 0.58%, respectively. Conclusion: According to ICH and FDA specifications, the optimized method was validated. The developed method was found to be appropriate for quantifying Vinamidinium hexafluorophosphate in Etoricoxib by employing LC-MS.
Keywords: Vinamidinium Hexafluorophosphate (VHP); Etoricoxib (ETC); International Conference on Harmonization; LC-MS/MS